The urban anthropologist as flâneur; The symbolic pattern of Indonesian cities - Nas, Peter J.M. (Wacana, Journal of the Humanities of Indonesia, 2012)
Cities are places full of symbols. In the past decades, Indonesian cities have become the cradle of urban symbolism studies. In this article, the author presents the results of these studies. The cities researched differ tremendously, ranging from the national capital to provincial capitals and small towns; some of them, such as Jakarta, are purely colonial in origin, while others are more or less traditional in character. Some of them have a top-down symbolic structure, largely the product of government activities, while others have symbolic configurations which have a more grassroots character and are based in the religious domain. The methodological aspect of urban symbolism fieldwork is explored by the introduction of the concept of fl neur.